Revolutionising multi-sectoral nutrition policy: Insights from the Ethiopian National Information Platform for Nutrition (NiPN) approach - Zerfu, Taddese Alemu; Tareke, Amare Abera; Genye, Tirsit; Bayable, Melaku; Muleta, Anbissa; Getu, Zekarias; Negese, Tarekegn; Darsene, Hiwot; Tessema, Bedassa; Molla, Dejen Tesfaw; Halala, Yoseph; Zewdu, Frezer; et al. (International Society of Global Health, 2024)
The global nutrition and food security crisis, characterised by troubling trends in various forms of malnutrition ranging from hunger to obesity, has significantly worsened [1,2]. In 2021 and 2022, nearly one-third of the global population faced moderate to severe food insecurity, underscoring a persistent challenge in accessing healthy and sustainable diets [1,3]. This decline in diet quality has led to a surge in malnutrition, with obesity and diet-related noncommunicable diseases (NCDs) reaching epidemic proportions [4–6].